Six Categories of Medical Uncertainty: A Framework for Emergency Medicine Education - Kenneth V. Iserson (Emergency Care and Medicine, 2026)
Background/Objectives: Medical training prepares students to diagnose known diseases and barely at all for the uncertainty that fills emergency practice, where symptom-based labels are common and nearly half of emergency medicine residents report difficulty discussing what remains unknown. This article sets out a six-category framework that separates medical uncertainty into distinct epistemological forms, so that communication can be matched to the uncertainty at hand. Methods: I used critical interpretive synthesis with iterative taxonomy development under prespecified ending conditions, arriving at six categories: (1) known and treatable, (2) unexplained, (3) untreatable, (4) heterogeneous, and (5) contested diseases, plus (6) depathologized conditions. Derivation ran iteratively against a purposive set of exemplar conditions, and existing uncertainty taxonomies were examined as alternatives. For each category I identified its epistemological features, the patient experience, and the communication it requires then built recommendations for teaching, assessment, and faculty development. Results: The framework supports structured reasoning and category-specific communication at three points in the emergency encounter: initial assessment, diagnostic testing, and disposition. Keeping a “known and treatable” category is what shows learners that apparently settled knowledge is provisional and context-dependent, which guards against false confidence. Categories are usefully assignable without being mutually exclusive; a condition may occupy several at once and may migrate as knowledge changes. Conclusions: The framework replaces generic advice to “tolerate ambiguity” with concrete tools for category recognition, emergency department safety-netting, disposition communication, and assessment. It is conceptually derived; its categories, scripts, and rubric require empirical validation through curriculum implementation and educational outcomes research.